Analysis of Relationships among the Subjective Well-Being, Life Satisfaction and Job Anxiety for the Undergraduate Psychology Students - Karayagiz, Saban (Progress in Nutrition, 2020)
Objective: This study was designed to explore job anxiety, life satisfaction, and subjective levels of well-being for the undergraduate students enrolled in the department of psychology at a university. Materials and Methods: Four data collection tools were implemented in addition to the sociodemographic data form when collecting data. The data collection instruments included Job Anxiety Questionnaire (JAQ), Subjective Well-Being Scale (SWS), Beck Anxiety Inventory (BAI), and Satisfaction with Life Scale (SWLS), respectively. Study Group: A total of 153 undergraduate students enrolled in the department of psychology at a private university in Kayseri, Turkey. 50 of them were freshman and 103 were senior students. Most participants (62%) consisting of the female. Findings and Discussion: The findings revealed that senior students had a moderate negative correlation between life satisfaction and job anxiety as well as anxiety levels. Furthermore, the subjective well-being of the participants was observed to positively affect their job anxiety levels through the last grade, on the other hand, a significant decrease appeared in the anxiety levels. Results and Suggestions: The rapid rise of subjective well-being levels for the senior year psychology students might be due to the training offered in their major. Besides, it was not surprising that seniors had higher levels of job anxiety near the graduation and anxiety levels decreased because of their training, education, and experiences accomplished in this context.